Kajian Fonetik Bunyi Vokal Tunggal Bahasa Mandarin - Lily Thamrin; Fika Tanira; Suhardi Suhardi (Universitas Mulawarman, 2023)
This study aimed at describing the characteristics and differences in the Mandarin vowel sounds. This study involved a Chinese lecturer and two students of Mandarin Language Education FKIP Untan as research samples. The research data was in forms of Mandarin vocabulary which contains a single vowel. The PRAAT application was used to calculate the time, frequency, and intensity of the research object when uttering single vowel words. This study used experimental phonetics as a research method and presented the data in forms of tables and spectrogram images. The data retrieval method is through the PRAAT program with audio files (MP3). The study results show that pronunciation of a single vowel sound /o/ with the longest duration value from students and native speakers. The highest pitch value for native speakers is 315 Hz in single vowel /i/ and the highest pitch value for students when pronouncing words with single vowel /o/, with a voice frequency of 279.5 Hz. The highest native intensity value is for single vowel /ε/ with a value of 79.92 dB, single vowel /o/ is 79.96 dB for student speakers. The influence of tone errors is one factor that affects the resulting duration, pitch, and intensity values.